Innovative Marketing Practices for Evolving Consumers - Agarwal, Vaishali (Indian Journal of Marketing, 2010)
Every decade since Indian independence has been marked by substantial shifts in the business environment of the nation. These transitions are very well visible in the marketing industry of that period too. The era from fifties to late sixties was marked by a shift from agricultural economy to industrial economy. Early seventies to late eighties heralded the age of growing professionalism and birth of many iconic Indian brands into the marketplace (Prasad, 2008). The post liberalization phase in India has gone through plenty of changes in the market place. This phase has not only spotted the massive inflow of brands coming from various countries all around the globe, but has also observed the changing consumers and evolving trends in the consumer behaviour. These transitions necessitated the shift from ’Production Oriented Marketing’ in early fifties to the ’Holistic Marketing’ in the contemporary times. Further, the technological advancements, media revolution, quality orientation, service work culture and unbeaten fierce competition have educated the customers like never before (Akula, 2008). This time period has seen lot many transitions in the market from the days of Nirma to Maruti Suzuki to Dabar lal dant manjan to Sunsilkgangofgirls.com (Agarwal, 2008). Present day customers have matured from those seeking satisfaction to those who want to be delighted by their marketers. The products needed, the brands desired, the way of approaching and consuming them have transformed radically. The latest socio-cultural trends of society, proliferating brands, and growing economy has created both opportunities and challenges for the marketers. Now marketers constantly have to think of innovative ways to reach the mind of customers (Jayswal & Salvi, 2007). As the marketing guru, Philip Kotler quoted, "Companies should think about the millennium as a golden opportunity to gain mind share and heart share". There is no rule of thumb to gain the heart and mind share; the marketers need to think out of the box for developing innovative products, discovering new channels for distributing them and exploring the complete 360 degrees of communication routes. The future of marketing is about ’mesmerization’ of customers; colours that hypnotize, fragrances that seduce, lights/sounds that ignite passion, create emotional attachments (Shukla, 2007). The modern day customers can be captivated by designing innovative products and implementing innovative marketing practices like ambient and digital media, creative product placements, permission marketing and e-stores to name a few.